Does the Combination of Anticoagulants and Angiogenesis Inhibitors Increase the Risk of Bleeding in Cancer Patients? - Chen, Qixin; Huang, Xiaoting; Lin, Shen; Luo, Shaohong; Nian, Dongni; Lin, Ningning; Weng, Xiuhua; Xu, Xiongwei (Thrombosis and Haemostasis, 2025)
The advent of angiogenesis inhibitors has expanded therapeutic options for tumors but poses challenges due to bleeding risks, especially in patients requiring anticoagulation therapy for cancer-associated hypercoagulability.This study aimed to evaluate whether combining anticoagulants with angiogenesis inhibitors increases bleeding risk in cancer patients.A network meta-analysis was conducted based on PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials to compare bleeding risks with angiogenesis inhibitors alone versus their combination with anticoagulants. Furthermore, a real-world cohort of 645 patients receiving antiangiogenic therapies between January 2010 and June 2024 was studied. Patients were separated into two groups according to whether they were receiving concomitant anticoagulants. The primary outcome was all-grade bleeding events.Of 2,644 patients from six studies included in network meta-analysis, all-grade bleeding events were found in 614 (23.2%) patients. The addition of anticoagulation to either high-dose bevacizumab (10 or 15 mg/kg) (OR 4.95, 95% CI: 2.68–9.42) or antiangiogenic tyrosine kinase inhibitors (OR 2.2, 95% CI: 1.08–4.44) significantly increased bleeding risk compared with antiangiogenic monotherapy, except for low-dose bevacizumab (5 or 7.5 mg/kg). In the cohort study, 163 patients matched in each group after propensity score matching weighting. Over a median follow-up duration of 56 days, there were 28 (17.2%) all-grade bleeding events during concurrent treatment and 16 (9.8%) all-grade bleeding events reported during antiangiogenic monotherapy.Adding anticoagulation to high-dose bevacizumab or antiangiogenic TKIs might increase bleeding risk compared with monotherapy. Conversely, anticoagulants appeared to be safe in patients receiving low-dose bevacizumab.
Keywords: angiogenesis inhibitors; anticoagulants; bevacizumab; hemorrhage; tyrosine kinase inhibitors